The Implementation of Augmented Reality Based on Vuforia and Unity for Interactive Learning in Introducing Ragam Randang Objects - Zulfadli, Zulfadli; Sunaryo, Budi; Wiyanatra, Reihan Hanafi; Sandra, Randi Proska (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
Augmented Reality (AR) is a technology that combines objects from the real world and virtual or virtual objects with real-time or direct conditions. The merging of real and virtual objects occurs because of the right technological support while the interactions that are carried out can occur using certain devices. AR is a variation of Virtual Environments (VE), better known as Virtual Reality (VR). This VR technology allows users to fully immerse themselves in a virtual environment. While Augmented Reality technology is developing very fast, many applications in Indonesia use AR technology. This study uses the waterfall system development method, where the research flow will follow the phases of the waterfall. This application is built using Unity and Vuforia. The purpose of this research is an interactive application to make it easier for students and museum visitors to understand augmented reality through mobile devices. So that museum visitors and students can see objects containing information interactively